Assessment of the Company’s Performance in Light of Delay in Managerial Information - Kubayev, Kazila Ð•rikenovich (International Journal of Economics and Financial Issues, 2016)
The goal of the study is to develop a theoretical framework for assessment of the speed of the company’s management system performance in light of its informational nature. The article uncovers a law of delay in managerial information and develops a theory of assessment of the speed of the company’s performance on the basis of experimental and theoretical study. It introduces new options of building the control systems "system pace" and other indicators arising out of the "system pace": time of the management cycle, stages and levels of management. The parameters of managerial information – the pace of reception, processing, reflection, decision-making and execution of the decision – were obtained theoretically and experimentally, using a well-known normal distribution law. The experiments that confirm the theory were taken. Keywords: company; management; information; delay; system JEL Classifications: D23, D83, D85